DETERMINANTS OF FAMILY ASSISTANCE TEAM CADRES’ PERFORMANCE IN THE STUNTING REDUCTION ACCELERATION PROGRAM IN TELUK PANDAN DISTRICT, PESAWARAN REGENCY - Barmawi, Destriani Aisyah; Dunan, Hendri; Oktaviannur, M (Program Studi Magister Manajemen, 2024)
The Family Assistance Team (TPK) cadres are established groups formed to support the national target of reducing stunting prevalence to 14% by 2024 across various regions in Indonesia, including Teluk Pandan District, Pesawaran Regency. Assessing the performance of TPK cadres is essential to evaluate their effectiveness in promoting behavioral changes within communities regarding child nutrition and health. This study aims to examine the influence of work experience, motivation, education, and skills on the performance of TPK cadres in assisting families at risk of stunting in the region. The research employed a quantitative approach using questionnaires distributed to the entire population of 54 TPK cadres, who also served as the study sample. The sampling technique applied was non-probability sampling through purposive sampling. Data analysis was conducted using descriptive statistics. The findings reveal that work experience, motivation, education, and skills collectively have a positive and significant effect on the performance of TPK cadres in supporting families vulnerable to stunting. These results highlight the need for regular monthly meetings and the provision of monitoring books as tools for ongoing evaluation of TPK cadre performance. Such measures help identify achievements, address emerging challenges, and implement necessary improvements to enhance the effectiveness of family assistance conducted by TPK cadres.